2018
DOI: 10.1016/j.ejmech.2017.11.080
|View full text |Cite
|
Sign up to set email alerts
|

Development of inhibitors of receptor protein tyrosine phosphatase β/ζ (PTPRZ1) as candidates for CNS disorders

Abstract: A new series of blood-brain barrier permeable molecules designed to mimic the activity of Pleiotrophin in the CNS has been designed and synthesized. These compounds exert their action by interacting with the intracellular domain PD1 of the Protein Tyrosine-Phosphatase Receptor Z1 (PTPRZ1), and inhibiting its tyrosine phosphatase activity. The most potent compounds 10a and 12b (IC = 0,1 μM) significantly increase the phosphorylation of key tyrosine residues of PTPRZ1 substrates involved in neuronal survival and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…5 c). To confirm the relevance of the modulatory effects of RPTPβ/ζ inhibition on LPS actions in microglial cells, we tested another inhibitor of RPTPβ/ζ: MY33-3 20 . The highest concentration of MY33-3 (10 μM) significantly limited both the LPS-induced nitrites production (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 c). To confirm the relevance of the modulatory effects of RPTPβ/ζ inhibition on LPS actions in microglial cells, we tested another inhibitor of RPTPβ/ζ: MY33-3 20 . The highest concentration of MY33-3 (10 μM) significantly limited both the LPS-induced nitrites production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies designed to test the effect of pharmacological inhibition of RPTPβ/ζ on LPS-induced neuroinflammation, Wt mice were administered 60 mg/kg MY10 or vehicle (10% dehydrated ethanol, 20% polysorbate 80, 70% PEG-400) by oral gavage in a volume of approximately 0.1 ml 1 h before a single IP injection of LPS (7.5 mg/kg) or saline (control). It was previously shown that the brain to plasma ratio is 3:1 1 h after intragastric administration of 60 mg/kg MY10 20 .…”
Section: Methodsmentioning
confidence: 93%
“…Blocking PTN‐PTPRZ1 signaling in animal models by shRNA or anti‐PTPRZ1 antibody potently suppressed glioblastoma tumor growth and prolonged animal survival . The selective inhibition of PTPRZ1 is a promising approach for glioma therapy .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that ethanol-induced activation of ALK signaling through MDK is indirectly caused by MDK binding to and inactivating RPTPβ/ζ. Of note, systemic treatment of mice with the RPTPβ/ζ inhibitor, MY10 [110], decreased binge ethanol consumption, reduced ethanol CPP, and enhanced the sedative effect of ethanol [106,111]. Treatment of neuroblastoma cells with MY10 or ethanol increased ALK phosphorylation as expected, but combined treatment of cells with MY10 and ethanol blocked the ethanol-induced increase in ALK phosphorylation [106], which might explain how MY10 is able to reduce drinking even though it is an inhibitor of RPTPβ/ζ.…”
Section: Alkmentioning
confidence: 99%